Dampak Budaya Organisasi, Motivasi dan Kepuasan Kerja terhadap Kinerja Karyawan - Azzizah, Septiana Nur; Gulo, Yupiter (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This study aims to analyze and determine the effect of organizational culture, motivation, and job satisfaction on the performance of production department employees at PT. Suzuki Indomobil Motor Plant Tambun II. Sampling using probability sampling technique with a total sample used as many as 104 respondents. Data collection was carried out by distributing questionnaires to all respondents. The method of data analysis in this study is using multiple linear regression. Prior to testing the hypothesis, data were analyzed using research instrument testing, classical assumption testing and model testing using statistical software programs. The results of this study indicate that organizational culture and motivation have a positive effect on employee performance. While job satisfaction has a negative effect on employee performance